Topological symmetry breaking of self-interacting fractional Klein–Gordon field theories on toroidal spacetime - Lim, S C; Teo, L P (IOP PUBLISHING LTD, 2008)
Quartic self-interacting fractional Klein-Gordon scalar massive and massless field theories on toroidal spacetime are studied. The effective potential and topologically generated mass are determined using zeta-function regularization technique. Renormalization of these quantities are derived. Conditions for symmetry breaking are obtained analytically. Simulations are carried out to illustrate regions or values of compactified dimensions where symmetry-breaking mechanisms appear.